Long-Term Cultivation of Human Atrial Myocardium - Klumm, Maximilian J.; Heim, Christian; Fiegle, Dominik J.; Weyand, Michael; Volk, Tilmann; Seidel, Thomas (Frontiers in Physiology, 2022)
Long-term organotypic culture of human ventricular cardiac tissue is an emerging tool in basic and translational cardiac research. However, only few institutions have access to human ventricular tissue, whereas atrial tissue is more commonly available. This study presents a method for long-term cultivation of beating human atrial myocardium. After written informed consent, tissues from the right-atrial appendage were obtained from patients with sinus rhythm undergoing open heart surgery with cardiopulmonary bypass. Trabeculae (pectinate muscles) prepared from the samples were installed into cultivation chambers at 37° C with a diastolic preload of 500 µN. After two days with 0.5 Hz pacing, stimulation frequency was set to 1 Hz. Contractile force was monitored continuously. Beta-adrenergic response, refractory period (RP) and maximum captured frequency (fmax) were assessed periodically. After cultivation, viability and electromechanical function were investigated, as well as the expression of several genes important for intracellular Ca2+ cycling and electrophysiology. Tissue microstructure was analyzed by confocal microscopy. We cultivated 19 constantly beating trabeculae from 8 patient samples for 12 days and 4 trabeculae from 3 specimen for 21 days. Functional parameters were compared directly after installation (0d) with those after 12d in culture. Contraction force was 384±69µN at 0d and 255±90µN at 12d (p=0.8, n=22), RP 480±97ms and 408±78ms (p=0.3, n=9), fmax 3.0±0.5Hz and 3.8±0.5Hz (p=0.18, n=9), respectively. Application of 100 nM isoprenaline to 11 trabeculae at 7d increased contraction force from 168±35µN to 361±60µN (p<0.01), fmax from 6.4±0.6Hz to 8.5±0.4Hz (p<0.01) and lowered RP from 319±22ms to 223±15ms. CACNA1c (L-type Ca2+ channel subunit) and GJA1 (connexin-43) mRNA expressions were not significantly altered at 12d vs 0d, while ATP2A (SERCA) and KCNJ4 (Kir2.3) were downregulated, and KCNJ2 (Kir2.1) was upregulated. Simultaneous Ca2+ imaging and force recording showed preserved excitation-contraction coupling in cultivated trabeculae. Confocal microscopy indicated preserved cardiomyocyte structure, unaltered amounts of extracellular matrix and gap junctions. MTT assays confirmed viability at 12d. We established a workflow that allows for stable cultivation of beating human atrial myocardium for up to three weeks and functional analysis. This method may lead to novel insights into the physiology and pathophysiology of human atrial myocardium.